Aplikasi Teknologi Dekomposer Rumen Sapi Pada Serasah Tanaman Di Kebun Gunung Pasang PDP Kahyangan Jember - Triono Bambang Irawan; Satria Indra Kusuma; Nuraisyah, Anni; Liliek Dwi Soelaksini (Politeknik Negeri Jember, 2022)
The Regional Plantation Company (PDP) Kahyangan Jember as a producer of Robusta coffee experienced a decline in profits. As a result of not fertilizing coffee plants, the production of PDP Kahyangan Jember coffee has decreased drastically. So far, Gunung Pasang PDP Kahyangan Jember gardens only use chemical fertilizers and never use organic materials to maintain soil fertility. The use of litter buried in the rorak around the coffee plant canopy is an alternative to increase soil organic matter and plant nutrients. Decomposer technology from cow rumen can be applied to accelerate the decomposition process of plant litter which can increase soil organic matter while providing nutrients or nutrients needed by plants. The objectives of this service are: (i) accelerating the process of decomposition and mineralization of plant litter; (ii) increase soil organic carbon and provide plant nutrients; (iii) improve growth and increase coffee crop production. The method of service is carried out, among others, namely: (i) counseling in the form of the importance of increasing soil organic matter around the coffee plant canopy and the role of decomposers from cow rumen to accelerate the process of decomposition and mineralization of plant litter as a provider of plant nutrients); (ii) training in the practice of making decomposers from cow rumen; (iii) apply the decomposer technology from cow's rumen to plant litter and evaluate the results of the application of decomposer technology from cow's rumen to plant litter. Through discussions and questions and answers between the Telecommunications Rumen Decomposer Technology Development Team at the State Polytechnic of Jember with the PDP Kahyangan Management Team and the Management of Gunung Pasang Jember Gardens, it was concluded that the application of cow rumen decomposer technology has been running smoothly and quite successfully and can be applied in plantation areas